Effectiveness and safety differences of isoxsuprine and nifedipine as tocolytics in the risk of preterm labor - Oktavia, Nur; Yulistiani, Yulistiani; Markus, Unedo H; Mamo, Hendriette Irene (Folia Medica Indonesiana, 2017)
Premature labor is a cause of high rates of perinatal morbidity and mortality. The use of tocolytics is one of the efforts to handle the risk of preterm labor. Tocolytics which are widely used in Indonesia is isoxsuprine and nifedipine. The purpose of this study was to identify the difference of effectiveness and safety of isoxsuprine as tocolytics in the risk of preterm labor. This was an observational study in the form of a case study that was done in detail and depth to the patients who were diagnosed as imminent preterm labor. In conclusion, there were differences in the effectiveness and safety of isoxsuprine and nifedipine as tocolytics in the risk of preterm labor.